Ammonia-oxidizing archaea and ammonia-oxidizing bacteria communities respond differently in oxy-gen-limited habitats - Du, Jialin; Meng, Lin; Qiu, Mingsheng; Chen, Shuaiwei; Zhang, Binghui; Song, Wenjing; Cong, Ping; Zheng, Xuebo (Frontiers in Environmental Science, 2022)
Ammonia-oxidizing archaea (AOA) and bacteria (AOB) are the most important ammonia oxidation functional community, while the coastal environment just provides a different oxygen environment for the ammonia oxidation process. However, few surveys concentrated on the influence of oxygen concentration on the niche specialization of AOA and AOB in the ocean intertidal zones. Here, high-throughput sequencing by Illumina MiSeq and qPCR were applied to detect the change of abundance, diversity as well as community structure of both AOA and AOB with 0–60 cm sediments depth in the intertidal zone in Qingdao, China. Results showed that the AOA/AOB amoA gene copy numbers and AOA/AOB OTU numbers rate increased as sediment depth went more profound, which indicated that AOA was more adaptive to oxygen-limited niches compared to AOB. Oxygen indeed led to the niche specialization of AOA and AOB in intertidal sediments. The dominant AOA and AOB were the clusters of Nitrosopumilus and Nitrosospira, respectively, which indicated ecological success in the intertidal zone. A significant and positive correlation (p < 0.01) between AOB abundance/AOB OTU numbers and Oxidation-reduction potential (ORP) was observed. In addition, both total nitrogen (TN) (p < 0.01) and pH (p < 0.05) were significantly negatively correlated to AOB abundance. TN was also significantly negatively correlated to AOB OTU numbers (p < 0.05). Hence, oxygen led to niche specialization of AOA and AOB, especially under anoxic conditions, AOA played a dominant role in the process of ammonia oxidation. The Nitrosopumilus and Nitrosospira clusters were the dominant AOA and AOB, respectively, representing an ecological success in the intertidal zone.